Participatory plant breeding programs - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
PPBs are based on dynamic collaboration between plant breeding institutions and farmers and are designed to ensure that research is directly relevant to farmers’ needs. As most of the programs take place in farmers’ fields, PPB programs can maintain and enhance agricultural biodiversity much more effectively than conventional breeding programs. ICARDA’s PPB programs are implemented in more than 50 villages in six countries (Algeria, Egypt, Eritrea, Jordan, Syria and Iran).